Does Doing Good Always Lead to Doing Better? Consumer Reactions to Corporate Social Responsibility - Sen, Sankar; Bhattacharya, C.B. (Journal of Marketing Research, 2001)
In the face of marketplace polls that attest to the increasing influence of corporate social responsibility (CSR) on consumers' purchase behavior, this article examines when, how, and for whom specific CSR initiatives work. The findings implicate both company-specific factors, such as the CSR issues a company chooses to focus on and the quality of its products, and individual-specific factors, such as consumers' personal support for the CSR issues and their general beliefs about CSR, as key moderators of consumers' responses to CSR. The results also highlight the mediating role of consumers' perceptions of congruence between their own characters and that of the company in their reactions to its CSR initiatives. More specifically, the authors find that CSR initiatives can, under certain conditions, decrease consumers' intentions to buy a company's products.